Implementasi Pembelajaran Berbasis E-learning pada Mata Pelajaran Pendidikan Agama Islam - Anif Rachmawati; Evi Fatimatur Rusydiyah (Program Pascasarjana Universitas Ibrahimy, 2020)
E-learning has an important role in Islamic Education learning. Students are expected to not only listening to the explanation of the material from the teacher but also playing an active role in learning by applying e-learning. This study aims to analyze the implementation of learning based e-learning in Islamic Education course. The method used in this research was qualitative descriptive. The subject of this study was SMK 8 Surabaya students for the Islamic Education course. The data collection method had been done by interview and documentation. Data analysis had been done by collecting data, reducing data, presenting data, and making conclusions. The results of this study were the researcher found three stages in learning-based e-learning in the Islamic Education course, which is planning stage, implementation stage, and evaluation stage.